VALUASI KONTINGENSI TERHADAP TUTUPAN TAJUK POHON AGROFORESTRI KAKAO (Theobroma Cacao,L) DI DESA MANTIKOLE KECAMATAN DOLO BARAT, KABUPATEN SIGI, PROVINSI SULAWESI TENGAH. - Lestari, Nina Eka; Umar, Syukur; Alam, Andi Sahri (Jurnal Warta Rimba, 2017)
This research aimed to find out the rate of valuation contingency towards canopy cover of cocoa agroforestry trees in Mantikole village West Dolo, Sigi District. This research applied contingency method or technique (contingent valuation method CVM) which was a direct calculating way by asking peoples readiness (Willingness to pay,WTP) in gathering data through survey, sometimes it was done by doing interview. While Willingness to Accept (WTA) was individual first utility of goods and services before there was any variable and individual willingness to accept compensation if the goods and the services used by another individual or its utility was changed. The result of regression analysis (Y) economic value in Mantikole village was affected by living cost factor (0,86594901X1), canopy cover (-0,076211633X2), income (0,002719734X3), land area (-1,071470904X4), family members (-1,882253198X5), age (0,154847899X6). If it was tested in combination and simultaneously, X1 variable (living cost) significantly affected, while X2 variable (canopy cover), X3 (income), X4 (land area), X5 (family members), X6 (age) insignificantly affected economic value. So that, canopy cover valuation of cocoa agroforestry (Theobroma Cacao,L) in Mantikole village was 8,187,755 Rupiahs and WTA (willingness To Accept) was  756,500,000 Rupiahs. The result was gained from simultaneously analysis of multiple linear regression; Y= 16.96806933 + 0.86594901X1 – 0.076211633X2 + 0.002719734X3 – 1.071470904X4 – 1.882253198X5 + 0.154847899X6.Kata Kunci: Contingency Valuation,  Tree Canopy, Agroforestry, Cocoa.